Conditional Loss of Hoxa5 Function Early after Birth Impacts on Expression of Genes with Synaptic Function - Lizen, Benoit; Moens, Charlotte; Mouheiche, Jinane; Sacré, Thomas; Ahn, Marie-Thérèse; Jeannotte, Lucie; Salti, Ahmad; Gofflot, Françoise (Frontiers in Molecular Neuroscience, 2017)
Hoxa5 is a member of the Hox gene family that plays critical roles in successive steps of the central nervous system formation during embryonic and fetal development. In the mouse, Hoxa5 was recently shown to be expressed in the medulla oblongata and the pons from fetal stages to adulthood. In these territories, Hoxa5 transcripts are enriched in many precerebellar neurons and several nuclei involved in autonomic functions, while the HOXA5 protein is detected mainly in glutamatergic and GABAergic neurons. However, whether HOXA5 is functionally required in these neurons after birth remains unknown. As a first approach to tackle this question, we aimed at determining the molecular programs downstream of the HOXA5 transcription factor in the context of the postnatal brainstem. A comparative transcriptomic analysis was performed in combination with gene expression localization, using a conditional postnatal Hoxa5 loss-of-function mouse model. After inactivation of Hoxa5 at postnatal days (P)1-P4, we established the transcriptome of the brainstem from P21 Hoxa5 conditional mutants using RNA-Seq analysis. One major finding was the down-regulation of several genes associated with synaptic function in Hoxa5 mutant specimens including different actors involved in glutamatergic synapse, calcium signaling pathway and GABAergic synapse. Data were confirmed and extended by RT-qPCR analysis, and the expression of several HOXA5 candidate targets was shown to co-localize with Hoxa5 transcripts in pre-cerebellar nuclei. Together, these new results revealed that HOXA5, through the regulation of key actors of the glutamatergic/GABAergic synapses and calcium signaling, might be involved in synaptogenesis, synaptic transmission and synaptic plasticity of the cortico-ponto-cerebellar circuitry in the postnatal brainstem.